Analysis of low-frequency oscillation characteristics and damping enhancement strategy for grid-forming PV with DC-voltage controller - Weikang Kong; Yongjun Zhou; Jun Li; Jie Wu; Jing Xia; Linpeng Lei (Frontiers in Energy Research)
IntroductionGrid-forming (GFM) converters with DC-voltage controller can emulate inertia and support frequency stability while maintaining a stable DC voltage, making this method well-suited for PV systems. However, the introduction of the DC voltage control loop exacerbates the issue of low-frequency oscillations in GFM converters. Although existing studies have identified negative resistance behavior through impedance analysis, t the overall impedance characteristics of the unit make it difficult to pinpoint the key sources of internal negative damping, posing challenges for the design of oscillation suppression strategies.MethodsBuilding on this, by applying the damping torque method, this paper analyzes the components of damping torque and synchronizing torque in DC-voltage controller based GFM (DC-GFM) converter and the stability conditions of multi-converter systems. This provides a clear explanation of the underlying mechanism behind negative damping and the influence of control parameters.ResultThe analysis reveals that the negative damping originates from the integral parameters in the DC-voltage controller. Based on this insight, a damping enhancement strategy for multi-DC-GFM system is proposed. The simulation results validate the effectiveness of both the parameter analysis and the proposed strategy.DiscussionFinally, the limitations of this paper and the future research directions are discussed.